2021
DOI: 10.1021/acschemneuro.1c00470
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Exploits Hidden Structural Features within the RNA Repeat Expansion That Causes c9ALS/FTD and Rescues Pathological Hallmarks

Abstract: The hexanucleotide repeat expansion GGGGCC [r­(G4C2)exp] within intron 1 of C9orf72 causes genetically defined amyotrophic lateral sclerosis and frontotemporal dementia, collectively named c9ALS/FTD. , the repeat expansion causes neurodegeneration via deleterious phenotypes stemming from r­(G4C2)exp RNA gain- and loss-of-function mechanisms. The r­(G4C2)exp RNA folds into both a hairpin structure with repeating 1 × 1 nucleotide GG internal loops and a G-quadruplex structure. Here, we report the identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 79 publications
2
12
0
Order By: Relevance
“…Our previous studies as well as those completed by others report that depending on the salt properties r(G4C2) exp prefers either a hairpin structure with repeating 1×1 G/G internal loops in syn-anti orientations (Figure 1AB) or a G-quadruplex structure 53 . Moreover, a small molecule, CB253, (Figure 1C) revealed formation of a minor and highly dynamic RNA structure, where the repeating 1×1 G/G loops transformed to 2×2 GG/GG due to strand slippage, which was detected by NMR spectroscopy 29 . Before investigating the structural properties of 2×2 GG/GG internal loops using T-REMD, we validated the RNA force field.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies as well as those completed by others report that depending on the salt properties r(G4C2) exp prefers either a hairpin structure with repeating 1×1 G/G internal loops in syn-anti orientations (Figure 1AB) or a G-quadruplex structure 53 . Moreover, a small molecule, CB253, (Figure 1C) revealed formation of a minor and highly dynamic RNA structure, where the repeating 1×1 G/G loops transformed to 2×2 GG/GG due to strand slippage, which was detected by NMR spectroscopy 29 . Before investigating the structural properties of 2×2 GG/GG internal loops using T-REMD, we validated the RNA force field.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that a small molecule, CB253 (Figure 1C), targeting r(G4C2) hexanucleotide repeat expansions associated with ALS/FTD can cause strand-slippage to transform the global RNA structure to an alternative form, which has 2×2 GG/GG internal loop motifs 29 . This internal loop motif is both transient and highly dynamic displaying rapid 1×1 G/G ↔ 2×2 GG/GG transformations, which prevents its characterization by traditional biophysical techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar strategy was recently used to lower the level of huntingtin mRNA and develop an innovative therapeutic approach against Huntington’s disease (Bhattacharyya et al, 2021). The rapid expansion of the field of RNA therapeutics correcting splicing has shown the potential of antisense oligonucleotide and small molecule splicing switches to induce targeted splicing correction and has provided novel therapeutic strategies for genetic diseases (Campagne et al, 2019a; Centa et al, 2020; Hua et al, 2011; Lentz et al, 2013; Naryshkin et al, 2014; Palacino et al, 2015; Ursu et al, 2021). In the future, it could also benefit cancer therapy.…”
Section: Discussionmentioning
confidence: 99%